2022
DOI: 10.1002/aenm.202202491
|View full text |Cite
|
Sign up to set email alerts
|

Organic‐Free and Lead‐Free Perovskite Solar Cells with Efficiency over 11%

Abstract: photovoltaic devices (23.3%), showing great potential toward practical applications. [1] However, thermal instability of organic components (e.g., methylammonium (MA) and formamidinium (FA)) and high toxicity of heavy metal lead (Pb) pose challenges for practical applications. [2][3][4][5] To address these issues, a new perovskite family of organic-free and lead-free cesium tin tri-iodide (CsSnI 3 ) has been proposed and attracted considerable attention. [6][7][8] One of the potential candidates within the new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…Chemie beneficial to the operational stability of Sn HaP solar cells, further research in this direction is needed. We expect these approaches to boost hole extraction in archetypal Sn HaP device architectures based on PEDOT:PSS and other less commonly employed HTLs such as nickel oxide (NiO x ) [83] or ambipolar tin oxide (SnO x ). [84] Recently, Song et al demonstrated the use of self-assembled monolayers (SAMs) on indium tin oxide (ITO) anodes in p-i-n, FASnI 3 -based solar cells.…”
Section: Methodsmentioning
confidence: 99%
“…Chemie beneficial to the operational stability of Sn HaP solar cells, further research in this direction is needed. We expect these approaches to boost hole extraction in archetypal Sn HaP device architectures based on PEDOT:PSS and other less commonly employed HTLs such as nickel oxide (NiO x ) [83] or ambipolar tin oxide (SnO x ). [84] Recently, Song et al demonstrated the use of self-assembled monolayers (SAMs) on indium tin oxide (ITO) anodes in p-i-n, FASnI 3 -based solar cells.…”
Section: Methodsmentioning
confidence: 99%
“…beneficial to the operational stability of Sn HaP solar cells, further research in this direction is needed. We expect these approaches to boost hole extraction in archetypal Sn HaP device architectures based on PEDOT:PSS and other less commonly employed HTLs such as nickel oxide (NiO x ) [83] or ambipolar tin oxide (SnO x ). [84] Recently, Song et al demonstrated the use of self-assembled monolayers (SAMs) on indium tin oxide (ITO) anodes in p-i-n, FASnI 3 -based solar cells.…”
Section: Minireviewsmentioning
confidence: 99%
“…In particular, Sn-based perovskite materials have been attracting a lot of interest since they share many of the same features as the other options and have shown the most promise in terms of device performance. The direct band gaps of these perovskites are significantly smaller and more appealing than those of their Pb-based counterparts, ranging from around 1.2–1.4 eV. , These perovskites exhibit direct band gaps between 1.2 and 1.4 eV, which are significantly smaller and more desirable than their Pb-based counterparts. Also, the all-inorganic Pb-free cesium tin triiodide (CsSnI 3 ) perovskite is currently the best candidate owing to its enhanced optoelectronic features, making it a potential alternative to Pb-based light absorption perovskites. , Substituting Cs for the organic cation in the perovskites has been shown to greatly improve their thermal stability and ambient cell performance .…”
Section: Introductionmentioning
confidence: 99%
“…23−25 The direct band gaps of these perovskites are significantly smaller and more appealing than those of their Pb-based counterparts, ranging from around 1.2−1.4 eV. 26,27 These perovskites exhibit direct band gaps between 1.2 and 1.4 eV, which are significantly smaller and more desirable than their Pb-based counterparts. Also, the allinorganic Pb-free cesium tin triiodide (CsSnI 3 ) perovskite is currently the best candidate owing to its enhanced optoelectronic features, making it a potential alternative to Pb-based light absorption perovskites.…”
Section: Introductionmentioning
confidence: 99%